Thirteen Plus One: A Comparison of Global Climate Policy Architectures - Joseph E. Aldy; Scott Barrett; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2003)
We critically review the Kyoto Protocol and thirteen alternative policy architectures for addressing the threat of global climate change. We employ six criteria to evaluate the policy proposals: environmental outcome, dynamic efficiency, cost effectiveness, equity, flexibility in the presence of new information, and incentives for participation and compliance. The Kyoto Protocol does not fare well on a number of criteria, but none of the alternative proposals fare well along all six dimensions. We identify several major themes among the alternative proposals: Kyoto is too little, too fast; developing countries should play a more substantial role and receive incentives to participate; implementation should focus on market-based approaches, especially those with price mechanisms; and participation and compliance incentives are inadequately addressed by most proposals. Our investigation reveals tensions among several of the evaluative criteria, such as between environmental outcome and efficiency, and between cost-effectiveness and incentives for participation and compliance.
Keywords: Q2; Q3; Q4; 330; Policy architecture; Kyoto Protocol; Efficiency; Cost effectiveness; Equity; Participation; Compliance; Klimaschutz; Umweltabkommen; Effizienz; Kosten-Wirksamkeits-Analyse; Gerechtigkeit; Ökosteuer; Welt; Clean Development Mechanism